Case Study of Product Line Approach to Provide Embedded and Desktop-Based Applications - Bellorini, Edmar; Oyamada, Marcio S.; Hexsel, Roberto A.; Giron, Alexandre A.; Gimenes, Itana M. S. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
The development of embedded systems requires methodologies to enable the integration of different levels of abstraction and able to deal with functional and non-functional requirements. Many methodologies are proposed like Software Product Line (SPL) and Model-driven Engineering (MDE), in order to reduce the complexity of the development process. This paper presents the use of a software product line approach for a digital magnifier development. The design flow starts from the specification using a SPL approach and follows a systematic set of steps to allow the application synthesis of desktop and embedded versions.